An overview of the Biosphere Reserve concept and its application to Nepal - Jha, Shree Gopal (Banko Janakari, 2007)
The present paper provides an overview on the concepts of biosphere reserves. The biosphere reserve concept has been developed within the framework of the UNESCO’s Programme on Man and Biosphere (MAB). The paper spells out definition, objectives, characteristics, function, beneficiaries, structure and design, and criteria for the selection of Biosphere Reserves etc. Key words: Biosphere reserve, conservation, ecosystem, conservation Banko Janakari Vol.16(1) 2006 pp21-24